PERSPEKTIF TEORI KEWENANGAN DEWAN PENGAWAS SYARIAH (DPS) DALAM RANGKA PENEGAKKAN PRINSIP-PRINSIP SYARIAH PADA LEMBAGA PERBANKAN SYARIAH - aryani witasari (UNISSULA, 2016)
Indonesia is the largest Muslim country in this world, since approximately 25 years ago trying to get out of the slump economic problems. One of the efforts was to fix the economic system by implementing Sharia system. The formulation of the problem is: What are the principles of Sharia to be enforced in the Islamic banking institutions? How theory perspective authority for DPS duty on Islamic banking institutions. Results shows that: general principles that must be upheld by Islamic banks is to avoid the usury and uses a system of revenue sharing as well as buying and selling. In order upholding Islamic principles that must be run by Islamic banks, it needs supervision that run by the Sharia Supervisory Board (DPS). DPS task as the supervisory board on Islamic banking is the attribution of authority. DPS is authorized by the original authority derived directly from law, Article 27 PBI No. 6/24 / PBI / 2004, which outlines the duties, powers and responsibilities of DPS, DPS Presence is what differentiates it from conventional banks. DPS is independent and equal position with BOC.